Tests of Deformation and Tensions in Reinforced Non-Cohesive Soil Layer - Surowiecki, Andrzej; Hutnik, Edward (Communications - Scientific letters of the University of Zilina, 2004)
The paper describes the results of laboratory testing of vertical deformations, horizontal pressure and vertical tensions on the close contact between reinforced non-cohesive soil layer and single-parameter subsoil. In particular, the diagrams of deformations and vertical tensions have been presented in the function of static load and reinforcement parameters. The following parameters have been also formulated: pattern to the calculation of coefficient of vertical tensions remittance and condition of equilibrium tensions in the reinforced soil model.